Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
:Table of Content • Using Advanced Artificial Intelligence Technologies to Improve Institutional Performance in Business Associations in Riyadh Ms. Mona Jeza Almutairi, Mr. Hassan Khidhr Alhallafi, Mr. Almotasim Khalil Alabbas • Applying lEAN Management Methods and Role to Achieving Administrative and Financial Performance in Business Organizations (Field Study) Asst-Prof. Dar Elneim Abakr Mohamed, Prof. Hoda Diab Ahmed • The Impact of Talent Management on Organizational Health: An Applied Study on Workers in the Emirate of Jazan Region Mr. Ghazwani, Ahmed Hassan, Prof. Alariki, Baseim Qaid • The Role of Strategic Management in Achieving Sustainable Development Goals Ms. Ibtesam Ahmed Al-Malkie, Co-Porf. Hasan Ahmed Al-Tally • Administrative leadership and its relationship to strengthening governance in local bodies in the Palestinian governorate of Qalqilya Lecturer Ala’ Yousef Najib Ashour • The impact of Technological development on the Growth of the manufacturing sector in gulf cooperation council countries Ms. Razan Mansour Hassan Almaiman, Co-Prof. Vivian Mohammed Saleh Nasrulddin • The Role of E-Government in combating Corruption in Syria Lawyer Animar Ali Zaher